Defining the Optimal Treatment Strategy in Patients With Uterine Serous Carcinoma. Issue 2 (February 2023) - Donkers, H.; Reijnen, C.; Galaal, K.; Lombaers, M.S.; Snijders, M.; Kraayenbrink, A.A.; Forrest, J.; Wilkinson, R.; Dubey, S.; Norris, T.; Bekkers, R.; Pijnenborg, J.M.A.; et al.
Abstract: Aims: Uterine serous carcinoma (USC) is an aggressive subtype of endometrial cancer with high rates of relapse and death. As adjuvant therapy might be beneficial in early-stage disease, the impact of standard complete surgical staging is questioned. Therefore, we wanted to explore the optimal treatment strategy for women diagnosed with USC. Materials and methods: A retrospective multicentre study of women diagnosed with primary USC in the UK and the Netherlands. Treatment strategy in relation to overall survival and progression-free survival was recorded and evaluated with Kaplan–Meier and Cox regression analysis. Furthermore, primary surgical staging and/or adjuvant treatment in relation to patterns of recurrence were evaluated. Results: In total, 272 women with a median age of 70 years were included. Most patients presented with International Federation of Gynecology and Obstetrics (FIGO) stage I disease (44%). Overall, 48% of patients developed recurrent disease, most (58%) with a distant component. Women treated with chemotherapy showed significantly better overall survival (hazard ratio 0.50, 95% confidence interval 0.31–0.81; P = 0.005) and progression-free survival (hazard ratio 0.48, 95% confidence interval 0.28–0.80; P = 0.04) in multivariable analysis. Furthermore, even in surgically staged women with FIGO stage IA disease, a high recurrence rate of 42% was seen. Conclusion: Women with USC who received adjuvant chemotherapy showed better survival rates compared with those who received other or no adjuvant treatment. The benefit of adjuvant chemotherapy was observed across all tumour stages, including surgically staged FIGO stage IA. These data question the role of surgical staging in the absence of macroscopic disease in USC. Highlights: Majority of women with recurrent USC present with distant disease. Women with USC, regardless of stage, benefit from adjuvant chemotherapy. Adjuvant chemotherapy seems superior to other adjuvant therapy in women with USC.